2006
DOI: 10.1111/j.1742-1241.2006.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing enlarged prostate in primary care

Abstract: Assessment and treatment of benign prostatic hyperplasia, or enlarged prostate, has evolved considerably in recent years; clear evidence has accumulated for the progression of disease over time, the association between disease progression and negative outcomes, and the potential for medical management of this condition. Commensurate with the long-term preventive role of primary care, efforts can and should be made to treat the underlying condition of enlarged prostate as well as to manage the symptoms short-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…It is also important to assess a patient's risk factors for progression of BPH. They include increasing age; EP (30 mL or more and PSA of 1.4 ng/mL or higher); moderate to severe symptoms (AUASI score higher than 7); signs of negative impact on quality of life (bother); and weak urinary fl ow [ 11 ].…”
Section: Evaluating Bph In the Primary Care Settingmentioning
confidence: 99%
“…It is also important to assess a patient's risk factors for progression of BPH. They include increasing age; EP (30 mL or more and PSA of 1.4 ng/mL or higher); moderate to severe symptoms (AUASI score higher than 7); signs of negative impact on quality of life (bother); and weak urinary fl ow [ 11 ].…”
Section: Evaluating Bph In the Primary Care Settingmentioning
confidence: 99%
“…The most important is that the authors believe that this clinical path is the most practical for the PCP, as minimal testing is required. It also follows typical practice patterns (4,28). Furthermore, an enlarged prostate may be the cause leading to the OAB.…”
Section: Provisional Bph: Behavioural and Pharmacological Therapymentioning
confidence: 99%
“…That being said, many feel that a "shared care" approach to the diagnosis and treatment of BPH should be adopted. 3,8 Primary care physicians are better positioned to identify men with LUTS and those at risk for disease progression, and should consider treatment for those men with mild to moderate symptoms without evidence of prostate cancer. In contrast, men with more severe symptoms requiring urgent or emergent treatment (such as surgery) should be seen by a urologist.…”
Section: S92mentioning
confidence: 99%
“…As a consequence, the initial management of BPH has shifted from the urologist to the family practitioner and other primary care physicians. 3,4 Subsequently, because of the rapidly increasing understanding of BPH and expanding treatment options, the Canadian and American urological associations were prompted to publish more relevant guidelines in 2005 and 2003, respectively. 5,6 Recent studies have demonstrated that the initial management of BPH may vary between the urologist and the primary care physician.…”
mentioning
confidence: 99%